THE ECOLOGICAL AND ECONOMIC STUDY OF WHITEFLY INSECTS (HEMIPTERA: PSEUDOCOCCIDAE) ON FRUIT MANGO - hakim, Lukmanul; Almukarramah, Almukarramah; Jailani, Jailani; Surya, Erdi (Universitas Serambi Mekkah, 2025)
Mealybug (Hemiptera:Pseudococcidae) is a polyphagous pest that attacks various horticultural crops. Its reproduction rate is very rapid; in tropical regions, the life cycle lasts about 19–25 days at temperatures of 28–32°C. Its natural enemies include predators and parasitoids. This study aimed to determine the number of colonies and individuals of the whitefly pest on mango plants. The research was conducted from July to November 2025 in Gampong Cot Mesjid, Lueng Bata District, Banda Aceh City, Aceh Province. The method used was qualitative with a descriptive approach, and data were collected through field observations. From five observed samples, the distribution of whitefly colonies on mango plants was found to be higher compared to the number of natural enemy individuals. The results showed a positive relationship between the number of whitefly colonies and the number of natural enemies; however, the effectiveness of natural enemies in suppressing pest populations remained low. Ecologically, maintaining a balance between pest and natural enemy populations is necessary. Economically, biological control needs to be strengthened to minimize losses caused by pests without dependence on chemical pesticides.